Modified Dorsal Split Preservation Hybrid Rhinoplasty for Cartilaginous Pushdown and Full Letdown Applications: A PROM-Based Review of 100 Consecutive Cases - Robotti, Enrico; Cottone, Giuseppe; Leone, Francesco (Facial Plastic Surgery, 2023)
Splitting the middle vault on an anatomical plane along the “Septal T” allows a new hybrid perspective on the many modifications of “surface” preservation techniques. The “dorsal split preservation” concept can be applied both to cartilaginous pushdown as well as to full letdown techniques. The dorsal keystone area is maintained, while the middle vault is reshaped. The septum is addressed by conventional L strut septoplasty. Precise direct suture fixation of the high-middle strip is easily accomplished after flexing the osseous-chondral junction at the K area. Specific technical points are described to allow exact and stable configuration of the dorsum.A retrospective analysis on 100 consecutive patients demonstrated aesthetic and functional improvement.
Keywords: rhinoplasty; preservation rhinoplasty; pushdown; nasal dorsum